Improving Students’ Vocabulary Mastery By Using Smile Game At SMP Swasta Hosana Medan - Indriani Sintiafeni Sinaga; Yenita Uswar (Universitas Muhammadiyah Enrekang, 2025)
This study aims to improve students' vocabulary mastery using the smile game at Hosana Private Junior High School, Medan. This study uses the Classroom Action Research (CAR) method, conducted in two cycles: cycle 1 and cycle 2, consisting of planning, implementation, observation, and reflection. Data were collected using observation sheets, interviews, and documentation. This analysis uses qualitative and quantitative analysis in student learning methods regarding the smile game method. The research subjects involved 25 eighth-grade junior high school students. The results showed that in the student learning test (pre- test), the average score obtained was 68.6. Then, in cycle I, the average score was 70.4, in cycle II, the average score was 76.4, and in the post-test, the average score was 80. The study concluded that students experienced significant improvement in the implementation of the Smile Game learning model from the initial to the final exam.